Association between nutrition-related indicators with the risk of chronic obstructive pulmonary disease and all-cause mortality in the elderly population: evidence from NHANES - Xu, Yifeng; Yan, Zhaoqi; Li, Keke; Liu, Liangji; Xu, Lei (Frontiers in Nutrition, 2024)
Background: This study aims to use six nutrition-related indicators to assess the relationship between nutritional status and the risk of COPD as well as the all-cause mortality rate, and to determine the most reliable predictive indicators. Methods: Data from the National Health and Nutrition Examination Survey (NHANES) spanning the years 2013 to 2018 were extracted. Nutritional status was evaluated using Controlling nutritional status index (CONUT) score, Geriatric Nutritional Risk Index (GNRI), Advanced Lung Cancer Inflammation Index (ALI), Prognostic Nutritional Index (PNI), Triglycerides (TG) × Total Cholesterol (TC) × Body Weight (BW) Index (TCBI), and Albumin-to-Globulin Ratio (AGR) nutritional-related indicators. Multivariate weighted logistic and Cox regression models were employed to assess the correlation between the six nutritional-related indicators and the risk of COPD and as all-cause mortality. The restricted cubic spline tests were applied to explore potential nonlinear relationships, and ROC curves and C-index analyses were conducted to compare the predictive capabilities of different indicators. Stratified analysis and propensity score matching (PSM) to assess the robustness of the results. Results: In this study, Lower ALI, lower GNRI, and higher CONUT scores were positively correlated with an increased risk of COPD (OR: 1.77, 95% CI: 1.10-2.84) (OR: 8.66, 95% CI: 2.95-25.5), and (OR: 5.11, 95% CI: 1.72-15.2), respectively. It was found that ALI and GNRI had a non-linear relationship with the risk of COPD. After propensity score matching (PSM), the associations between ALI, GNRI, CONUT scores, and COPD remained consistent. Lower ALI, PNI, and GNRI scores were positively associated with all-cause mortality in COPD patients (HR: 2.41, 95% CI: 1.10-5.27), (HR: 3.76, 95% CI: 1.89-7.48), and (HR :4.55, 95% CI: 1.30-15.9), respectively, with GNRI displaying a non-linear relationship with all-cause mortality. ROC curve and C-index analyses indicated that ALI had the best predictive ability for both COPD risk and all-cause mortality. Conclusion: ALI, GNRI, and CONUT scores are correlated with the risk of COPD, while ALI, PNI, and GNRI scores are associated with all-cause mortality in COPD patients. Compared to other nutritional scores, ALI may provide more effective predictive value for both risk and all-cause mortality.